Pleuropulmonary paragonimiasis with migrated lesions cured by multiple therapies - Yun Hu; Jun Qian; Dongliang Yang; Xin Zheng (Indian Journal of Pathology and Microbiology, 2016)
Paragonimiasis is an infectious disease caused by Trematodes of the genus Paragonimus that is endemic in Asia, Africa, and South America. Most patients with paragonimiasis are cured by standard praziquantel treatment. However, several cases have been reported to have unsatisfactory responses to the standard praziquantel treatment. To probe the clinical characteristics, possible cause, and management of the paragonimiasis individuals improved by multiple therapies, we present a 12-year-old Chinese boy, who was infected with Paragonimus accompanied by arachnoid cyst involvement, as not having typical clinical symptoms, but repeatedly presenting with migrated lesions between the lung and pleura. He responded to treatment with 3 cycles of praziquantel and 1 cycle of albendazole.